Parental involvement of marginalized children’s education in Yogyakarta - Serafin Wisni Septiarti; Farida Hanum; Siti Partini Suadirman; Erma Kusumawardani (LPMPP Universitas Negeri Yogyakarta, 2022)
Families living in slum areas are exposed to dense population and low income, both of which are conditions that make it difficult to meet the educational needs of their children. This article describes the involvement of parents in educating their children at home and at school. The study was carried out using ethnographic methods with 33 marginal families as informants. Marginal families who have children of elementary school age in grades 5 and 6, especially those living on the outskirts or banks of the Winongo and Code rivers, 3 large rivers that seem to divide the city of Yogyakarta, were included in this study. Data were collected using interviews, observations and focus groups. The results of the study show parental involvement as a form of transformation of knowledge systems, values, attitudes and skills. This often occurs in a patterned manner, repeatedly using examples, sometimes coercion as educational praxis at home and school in specific social environment situations. The daily interaction between parents and children in parent-child conversations tends to be instructive and emphasizes compliance to fulfill children's educational needs.